ISLAMIC EDUCATION IN THE TIME OF COVID IN MADRASAH IBTIDAIYAH SWASTA BALIGE (MIS BALIGE) - Ayu Mardiyatin Zanah Nurhikmah; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
Covid 19 or often said as the Corono outbreak is an epidemic that is very dangerous to health. In an effort to deal with the increasingly widespread corona virus outbreak, the government is encouraging people to implement social distancing or social restrictions. Thus, it has an impact on the world of education without exception at Balige Private Madrasah Ibtidaiyah (MIS Balige) but also applies online learning through electronic media. Although the network in Balige is fine, the problem is the inability of parents to buy electronic devices (Gadgets) for their children, but there are also some problems, namely, some parents do not understand technology so that many students do not actively learn through this method. The purpose of this paper is to determine the impact of Islamic religious education at MIS Balige during the COVID 19 pandemic. The research subjects of this study also include teachers and students of MIS Balige Pusat. The method used is a qualitative method in the form of a case study.Keywords: Covid 19, The Influence of Education in MIS Balige